1998
DOI: 10.1002/(sici)1097-0142(19980401)82:7<1233::aid-cncr4>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in surgical treatment have improved the survival of patients with gastric carcinoma

Abstract: It was concluded that survival has been improved by recent advances in the surgical approach to gastric carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…21,22 However, there are studies showing that the degree of lymph node dissection was a significant factor correlated with the survival time after curative resection for gastric cancer. 6,23,24 The current study revealed that lymph node metastasis is the most important factor predicting the timing of recurrence, and patients with lymph node involvement more frequently died of recurrence within 2 years after curative gastrectomy for gastric cancer. Intergroup-0116, a prospective multi-institution phase III trial evaluating postoperative combined chemoradiation versus surgery alone in 556 patients with completely resected stage IB to stage IV M0 adenocarcinoma of the stomach and gastroesophageal junction, reported a significant survival benefit with adjuvant combined-modality therapy.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 However, there are studies showing that the degree of lymph node dissection was a significant factor correlated with the survival time after curative resection for gastric cancer. 6,23,24 The current study revealed that lymph node metastasis is the most important factor predicting the timing of recurrence, and patients with lymph node involvement more frequently died of recurrence within 2 years after curative gastrectomy for gastric cancer. Intergroup-0116, a prospective multi-institution phase III trial evaluating postoperative combined chemoradiation versus surgery alone in 556 patients with completely resected stage IB to stage IV M0 adenocarcinoma of the stomach and gastroesophageal junction, reported a significant survival benefit with adjuvant combined-modality therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the emphasis on regular cancer screening programs and advances in diagnostic techniques has greatly improved the detection rate of early gastric cancer (EGC) [2]. In Korea, a population-based mass-screening program for GC was initiated by the Ministry of Health and Welfare in 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Although this screening program does not completely cover the target population, it already has led to an increase in the detection rate of EGCs from 33% in 1999 to 60% in 2012, and has subsequently contributed to an improved clinical outcome for GC [4]. In addition, advances in surgical techniques and multimodal treatments have also improved survival [2,5,6]. Because of this prolongation in survival, GC patients live longer, but have a greater possibility of developing multiple primary cancer (MPC).…”
Section: Introductionmentioning
confidence: 99%
“…With the increased detection of early gastric cancer and the improvement of surgical procedure during the past three decades (1-3), gastric cancer survival has improved. Long-term follow-up for recurrence has led to an increased incidence of second primary cancers (4,5).…”
Section: Introductionmentioning
confidence: 99%